Shallot의 우량종구 미세증식방법 개발 - 조용조(Yong Cho Cho); 문진성(Jin Seong Moon); 송주연(Ju Yeon Song); 정병룡(Byoung Ryong Jeong) (Weon'ye gwahag gi'sulji, 2007)
1995년 프랑스산 shallot을 도입하여 양파연구소에서 국내 적응을 수행한 결과 노지 월동작물로서 재배적인 가치가 있음이 밝혀졌다. 그러나 비대기의 고온에 의한 식물체의 조기 고사현상 및 습해 발생으로 수량이 점차 감소되는 것과 영양번식체로 세대를 진전시키는데 기인한 종구의 퇴화현상과 같은 어려움이 있었다. 이러한 문제점을 해결하기 위하여 shallot을 조직배양을 통해 유전적 동일성이 결여된 변이체가 발생되지 않는 virus-free 개체를 획득하기 위해 배양법별 우량 종구의 대량증식을 위한 연구를 수행하였다. 단축경배양은 다른 배양에 비하여 잎과 뿌리의 분화가 빠르고 구 비대 역시 빨랐다. 그리고 유전적으로 안정된 동질한 유식물체를 얻을 수 있었다. 화기배양은 치상 30일 후에 multiple shoots을 형성하여 대량증식의 좋은 재료임이 증명되었으나 소구의 형성기간은 단축경배양에 비하여 더 길었다. 치상에서 순화종료까지의 소요일수가 단축경배양은 140일, 화기배양은 250일, 그리고 생장점배양은 320일이어서 단축경배양이 생장점배양이나 화기배양에 비하여 각각 1.8배와 2.3배로 배양속도가 빨랐다. 한편, 증식력은 화기배양에서 4~13배로 가장 높았다. 그리고 virus-free 개체를 획득하기 위해서는 생장점배양이 요구되었다. 이상의 결과에서 virus- free 개체 획득을 위해서는 생장점배양이 좋으나 배양기간이 길고 증식력도 낮은 결점이 있었다. Shallot is a foreign crop introduced from France in 1995 as a new overwintering field crop with a aim to develop into an export crop. During the introductory cultivation trials, several problems were raised such as premature growth depression in early summer, sensitivity to summer moisture, and weakened vigor of the seed bulbs following successive propagations. This study was conducted to suggest cultural and propagational solutions to these problems. Genetically stable plantlets were obtained by the basal plate culture. Floral organ culture was considered as a good method because it produced plantlets with multiple shoots after 30 days in culture. However, more time was required for bulblet formation than in the disc culture. It took 140 days to obtain seed bulblets in the basal plate culture, 250 days in the floral organ culture, and 320 days in the meristem culture. Total number of days taken for micropropagation in the basal plate culture was 56% and 44% of that in the floral organ culture and meristem culture, respectively. On the contrary, the speed of propagation of the floral organ culture was 4 to 13 times as high as that of the basal plate culture. To summarize, meristem culture was good for obtaining virus-free bulbs, but was limited by a long culture period and a low propagation speed. KCI Citation Count: 5